Haemodynamically proven pulmonary hypertension in a patient with GATA2 deficiency-associated pulmonary alveolar proteinosis and fibrosis. Issue 5 (11th May 2017) - Jouneau, Stéphane; Ballerie, Alice; Kerjouan, Mallorie; Demant, Xavier; Blanchard, Elodie; Lederlin, Mathieu
Over the past few years, genetics has significantly improved the understanding of interstitial lung diseases (ILD). For example, in idiopathic pulmonary fibrosis, telomerase complex mutations have been shown to drive a specific phenotype including haematological, liver and cutaneous abnormalities [1]. Recently, GATA2 deficiency has been associated with a broad phenotype including haematological, vascular, infectious and pulmonary diseases [2–4]. GATA2 is a zinc finger transcription factor essential for differentiation of immature haematopoietic cells. Among many other functions, GATA2 regulates the phagocytosis of alveolar macrophages. Therefore, alveolar macrophage dysfunction is thought to be the pathophysiological basis for the occurrence of pulmonary alveolar proteinosis, the main lung condition in GATA2 deficiency [4]. However, pulmonary alveolar proteinosis associated with GATA2 deficiency does not share the same clinical, biological or radiological features as autoimmune pulmonary alveolar proteinosis. In all cases of GATA2 deficiency-associated pulmonary alveolar proteinosis reported in the literature, granulocyte–macrophage colony-stimulating factor (GM-CSF) antibodies were absent [2, 4]. Moreover, other pulmonary diseases such as fibrosis or pulmonary hypertension (PH) have been reported to occur in GATA2 deficiency [4], suggesting that the precise pathophysiological mechanisms are not fully understood. Pulmonary fibrosis may be more prevalent in adults with GATA2 deficiency due to a longer duration of the disease http://ow.ly/WHnu30aCZ4S